2008
DOI: 10.1111/j.1464-5491.2008.02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic accidents and diabetes: insulin use does not determine risk

Abstract: Our findings suggest that insulin-treated patients as a group do not pose an increased risk to road safety. They reiterate the need for an individualized risk-based assessment when considering driving restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…63-89 The included studies spanned from 1992-2013. Of these studies, eight (29.6%) were conducted in Norway, 69,70,72,73,75,77,79,82 six (22.2%) in the United States, 63,64,81,83-85 five (18.5%) from Canada, 65,66,86-88 three (11.1%) from England, 71,74,76 three (11.1%) from France, 67,78,80 one (3.7%) from the Netherlands, 68 and one (3.7%) from Taiwan. 89 Eleven (40.7%) of these studies were cohort designs, while the rest consisted of case-control or variations of a case-control design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…63-89 The included studies spanned from 1992-2013. Of these studies, eight (29.6%) were conducted in Norway, 69,70,72,73,75,77,79,82 six (22.2%) in the United States, 63,64,81,83-85 five (18.5%) from Canada, 65,66,86-88 three (11.1%) from England, 71,74,76 three (11.1%) from France, 67,78,80 one (3.7%) from the Netherlands, 68 and one (3.7%) from Taiwan. 89 Eleven (40.7%) of these studies were cohort designs, while the rest consisted of case-control or variations of a case-control design.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated three antihyperglycemic medications which included Insulin, 66,71,75,84,85,88 Metformin, 88 and Sulfonylurea 88 (Figure 6). Of the six studies that reported outcome measures for Insulin, only two reported a statistically significant increase in MVC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some published studies indicated that drivers with type 1 diabetes have a slightly higher risk, with a relative risk ratio of ;2 (7,8,9), but this was not confirmed by other studies (10). Two studies even suggested that there is no increased risk associated with insulintreated diabetes (11,12), but the methodologies used have been criticized (13).…”
Section: Understanding the Risk Of Diabetes And Drivingmentioning
confidence: 99%
“…It has been reported in the past in the UK to justify a plea of not guilty based on hypoglycemia unawareness [7]. Because of their propensity to develop hypoglycemia, diabetic patients are more likely to be involved in an accident during driving only slightly more than the rest of the population [8,9]. …”
Section: Neuroglycopaenia Automatismmentioning
confidence: 99%